Analisis Risiko Dalam Akad Shirkah Musyarakah Mutanaqisah Pada Perbankan Syariah - Sapitri, Niluh Anik; Patimari, Siti; Aswad Latipa, A. Hijratulh (JUMABI: Jurnal Manajemen, Akuntansi dan Bisnis, 2025)
The Shirkah Musyarakah Mutanaqisah (MMQ) contract is one of the leading products in Islamic banking that prioritizes the principles of partnership and justice in financing. This study aims to analyze various risks associated with the implementation of MMQ contracts in Islamic banking, as well as evaluate risk mitigation strategies that can be applied. The identified risks include credit, market, operational, legal, reputational, technology, human resources, and environmental risks. Each type of risk has the potential to have a significant impact on the success of the contract, so effective risk management is important. This study uses a qualitative method with a literature review approach to collect data from various relevant sources. The results of the analysis show that risk mapping and the development of appropriate mitigation strategies can increase trust between banks and customers. In addition, the active role of customers in understanding risks and compliance with sharia principles is also very important in achieving the success of the MMQ contract. With a collaborative and transparent approach, this contract is expected to provide greater benefits in the sustainable development of the business sector. This research is expected to make a positive contribution to the development of literature on Islamic banking risk management and become a reference for practitioners in improving the effectiveness of MMQ products.